Need for measurement of the innovation at Hungarian SMEs - Badics, Zsuzsa (Acta Agraria Debreceniensis, 2014)
Competitiveness studies have shown that innovation could be breakout point for some economies, regions and enterprises. Knowledge acquisition, creation and exploitation of the knowledge base have been an essential element for economic growth. These knowledge-based economic processes come together with the innovation. Measurement of innovation by indicators has been playing a really emphatic role in making strategy whether it is national or EU planning. Enterprises have always tried to measure and quantify their innovation activities mostly through the results of their economic process. Companies have generally considered their products as part of the innovation. That was the reason that in most cases they only and exclusively focused on the finished product. Some of them was able to realize that details of the production process must be taken into account in order to the whole innovation activity could be measured. That is why I find it important to examine of what the innovativity of enterprises is made of, and in which way they can be measured. In addition I was looking for the answer to the questions that how much the measuring method allows you to compare enterprises for further examination. The development of measurement methods is an essential moment of the article. As it is compiled for me the most important aspect of innovation, according to the statistical document, the Oslo manual guides you through the measurement methods and operational processes They play a very important role in proving my hypothesis. Overall, our country’s innovation results show those areas where we have high endowments, and also those where are the weaknesses. Of course, systems and tools defined by the governing authorities of national economies will have the main role but the activity of the European Union will be the frame in the end, because without subsidies from the EU budget, national budget wouldn’t be enough to implement these aims.